Intake and performance of confined crossbred heifers fed different lipid sources - Fiorentini, Giovani [UNESP]; Santana, Márcia Cristina Araújo [UNESP]; Sampaio, Alexandre Amstalden Moraes [UNESP]; Reis, Ricardo Andrade [UNESP]; Ribeiro, Andressa Ferreira [UNESP]; Berchielli, Telma Teresinha [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate the effect of different lipid sources on nutrient intake, performance, development and carcass characteristics of heifers raised in confinement. Twenty-one crossbreed heifers (Nellore × Santa Gertrudis × Braunvieh) received 600 g/kg forage composed of corn silage and 400 g/kg concentrate with a 58.0 g/kg fat content in the total diet. The following lipid sources were used: soybeans, protected fat (Megalac-E®) and soybean oil. The experimental design was completely randomized, with three treatments and seven replicates, and the means were compared by the Tukey test at 5%. The protected fat diet resulted in a greater intake of dry matter (8.80 kg/d) when compared with the other diets. The animals that were fed the protected fat diet had a higher average daily weight gain and slaughter weight. Feed conversion and protein efficiency rate were not influenced by lipid sources. Carcass yield was not influenced by the different diets.
Keywords: Carcass; females; Ingestion; protected fat; soy oil and soybean